Improvement Of Frontal Lobe Dysfunction And White Matter Integrity By rTMS In Treatment-Resistant Depression - Tateishi, Hiroshi (Neuropsychiatr Dis Treat, 2019)
AIM: The impairment experienced by many individuals with depression is closely related to the cognitive symptoms of the disorder. Repetitive transcranial magnetic stimulation (rTMS) is a noninvasive brain stimulation method providing a promising technique for improving cognitive symptoms in treatment-resistant depression (TRD). In the present study, we investigated whether a relationship exists between improvements in frontal lobe dysfunction induced by rTMS and improvement of white matter integrity revealed by diffusion tensor imaging (DTI) in TRD patients receiving rTMS treatment. METHODS: A total of 12 patients with TRD were enrolled in a high-frequency (10 Hz) rTMS study (August 2013–January 2019). Frontal lobe function and depressive symptoms were assessed at baseline and at the endpoint of rTMS treatment. Fractional anisotropy (FA), as a measure of white matter integrity obtained from DTI, was investigated using a region-of-interest (ROI) approach. RESULTS: rTMS treatment significantly improved depressive symptom scores and some subscales of frontal lobe dysfunction. Category scores in the Word Fluency Test and scores on part 3 of the Color Stroop Test were improved independently of the improvement of depressive symptoms. In the ROI analysis, none of the FA increases in any region were correlated with improvement of any frontal lobe function (n = 12). CONCLUSION: Although rTMS resulted in partial improvement of frontal lobe dysfunction as well as white matter integrity, we found no correlation between improved frontal lobe dysfunction and improved white matter integrity in TRD patients.